Ethical Tensions Resulting from Interpreter Involvement in the Consent Process. Issue 4 (23rd July 2019) - Barwise, Amelia; Sharp, Richard; Hirsch, Jessica
ABSTRACT: We describe how our institution responded when an interpreter who participated in the consent process involving an individual with limited English proficiency refused to cosign consent documents attesting that the individual enrolling in the study understood the consent information and that her consent to enroll was voluntary. In developing our approach, our institution took into account ethical tensions between the Belmont principles of respect for persons, beneficence, and justice that apply to the protection of research participants and the professional principles of beneficence, fidelity, and respect for the importance of culture that are outlined in ethical guidelines for medical interpreters.